Komparasi Perubahan Tutupan Lahan di Gili Meno, Gili Trawangan dan Gili Air (Gili Matra): Comparison Land Cover Change in Gili Meno, Gili Trawangan dan Gili Air (Gili Matra) - Lalu Arifin Aria Bakti; Siska Ita Selvia; Sukartono Sukartono; Suwardji Suwardji; Bambang Hari Kusumo (LPPM Universitas Mataram, 2023)
This research aims to determine changes in land cover on Gili Meno, Gili Trawangan, and Gili Air as small islands in West Nusa Tenggara Province. The method used in this research is a qualitative descriptive method in comparing land cover changes on each island and also spatial analysis using Google Earth satellite image data in 2013 and 2022. The research results show seven land cover classifications consisting of built-up land, open land, stretches of beach sand, water bodies, plantations, bushes, and mangroves. Based on the analysis of land cover changes in Gili Trawangan, Gili Meno, and Gili Air, a trend of increasing built-up land area for ten years from 2013 to 2022. The most significant increase in built-up land occurred on Gili Trawangan, namely 48.14 Ha. It was followed by Gili Air and Gili Meno, respectively 24.86 ha and 23.71 ha. The driving factor for changes in land cover on Gili Matra is policies from the central, provincial, and regional governments regarding the promotion and establishment of Gili Matra as a tourism destination in NTB Province. Furthermore, this policy impacts the growth of tourists and the number of residents. It causes an increase in the need for tourism-supporting facilities. Therefore, there is a change in land cover, which gradually reduces the area of undeveloped land on Gili Matra.